Monitoring of adipogenic differentiation at the single-cell level using atomic force microscopic analysis. Issue 6 (2011) - Kwon Kwon, Young-Nam Young-Nam; Kim Kim, Won Kon Won Kon; Lee Lee, Sang-Hak Sang-Hak; Kim Kim, Keewon Keewon; Kim Kim, Eun Young Eun Young; Ha Ha, Tai Hwan Tai Hwan; Han Han, HyoukSoo HyoukSoo; Bae Bae, Kwang-Hee Kwang-Hee
Abstract : Adipogenesis plays an important role in energy homeostasis by storing excess energy as lipid droplets. However, these reservoirs are implicated in a host of major human health problems, such as obesity. Elucidation of the mechanisms underlying adipogenesis is thus crucial to overcome these problems. The preadipocyte cell lines represent an optimal model to examine adipogenesis. Cells differentiate into adipocytes with various speeds of conversion and fat accumulation. Here, we have presented a novel method for detecting adipogenic differentiation at the single-cell level using atomic force microscopic analysis. Data obtained with this method revealed a good correlation between membrane stiffness and the degree of adipogenic differentiation. Although we could not determine the underlying cause for membrane stiffness reduction during adipogenic differentiation, the technique clearly offers advantages over the existing detection systems, such as lipid drop staining and extraction. Furthermore, the degree of adipogenic differentiation at the single-cell level can be detected with this method.